1972
DOI: 10.1002/1097-0142(197210)30:4<875::aid-cncr2820300402>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Infectious mononucleosis prior to acute leukemia: A possible role for the epstein-barr virus

Abstract: Three cases of ALL preceded by IM are reported. One patient developed leukemia associated with an apparent recurrence of IM 17 months later. The other two patients, who were diagnosed as having IM one month prior to the appearance of their leukemia, had a poor response to chemotherapy and died after a brief illness. All patients had antibody to the EBV viral capsid antigen, and two had antibody to the EBV‐associated early antigen. Although IM and ALL are suspected of being caused by a virus, epidemiologic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The presence of EB-virus-specific IgM antibodies in patients with active IM, where the EB virus is the known cause (Henle, Henle, and Deihl, 1968;Evans, Niedermann, and McCollum, 1968), and not in those with rubella or other infections is therefore not surprising and confirms the reliability of our methods. Their persistence in patients tested long after apparent recovery was not entirely unexpected, for total IgM levels in these patients may remain raised for up to 2 years after apparent recovery and virus may be excreted orally for several months (Miller, Niedermann, and Andrews, 1973;Golden et al, 1973). These raised total IgM levels were not associated with persistence of autoantibodies (such as those to smooth muscle) which are frequently found in patients with IM (Sutton et al, 1974c).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of EB-virus-specific IgM antibodies in patients with active IM, where the EB virus is the known cause (Henle, Henle, and Deihl, 1968;Evans, Niedermann, and McCollum, 1968), and not in those with rubella or other infections is therefore not surprising and confirms the reliability of our methods. Their persistence in patients tested long after apparent recovery was not entirely unexpected, for total IgM levels in these patients may remain raised for up to 2 years after apparent recovery and virus may be excreted orally for several months (Miller, Niedermann, and Andrews, 1973;Golden et al, 1973). These raised total IgM levels were not associated with persistence of autoantibodies (such as those to smooth muscle) which are frequently found in patients with IM (Sutton et al, 1974c).…”
Section: Discussionmentioning
confidence: 96%
“…Apart from showing infection in the leukaemic children, there were other reasons for suspecting that the EB virus might be associated with this immunological abnormality. The EB virus is associated with malignant disease and with IM; patients with IM have high levels of IgM (Wollheim and Williams, 1966;Sutton et al, 1973), produce autoantibodies, including antibodies to smooth muscle (Holborow, Hemsted, and Mead, 1973;Sutton et al, 1974c) which have also been observed in malignant disease (Whitehouse and Holborow, 1971), and may have temporary impairment of cell-mediated immunity (Haider et al, 1973), of possible significance in oncogenesis (Keast, 1970); following IM there is an increased risk of developing malignant lymphomata and, rarely, IM may be followed by leukaemia (Connelly and Christine, 1974;Levine et al, 1972).…”
mentioning
confidence: 99%
“…Raised titres of Epstein-Barr virus an,tibodies may be found in patients with Hodgkin's disease (Levine et al, 1971), though Goldman and Aisenberg (1970) did not find them. Isolated cases of leukaem-ia and Hodgkin's disease af,ter infectious mononucleosis have been repor,ted (English, 1970;Levine et al, 1972), and four out of .a series of 516 cases of Hodglin's disease developed subsequent to infectious mononucleosis (Smithers, 1967). Kaplan (1972) saw 37 cases of Hodgkin's disease with a fairly definite history of infectious mononucleosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been detected in leukaemic cells (Hehlmann, Kufe, and Spiegelman, 1972b) and antigenic relations have been observed (Mann, Halterman, and Leventhal, 1973) between acute leukaemic cells and cells infected with Rauscher leukaemia virus. Patients with infectious mononucleosis have been known to develop Hodgkin's disease (English, 1970), Burkitt's lymphoma (Cohen et al, 1970), and acute leukaemia (Levine et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…This speculation has not been supported by studies with the EB virus, the causative agent of infectious mononucleosis, and infections with this virus are not uncommon during the course of acute leukaemia (Stevens et al, 1971). Nevertheless, the relation of the EB virus to malignant disease and recent reports of infectious mononucleosis being followed closely by leukaemia (Levine et al, 1972) prompted further investigation in this field. .…”
mentioning
confidence: 98%